(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article examines the phenomenon of youth slang through the prism of gender linguistics. The key differences in the speech behavior of boys and girls, their communicative preferences, the subject matter of statements and the features of slang lexemes are analyzed. Special attention is paid to the history of the study of gender aspects of language, starting from foreign studies of the second half of the 20th century to modern domestic works. The article substantiates the conclusion that gender differences in youth slang not only reflect social roles, but also form new models of linguistic identity.